Assessment of Anxiety and Depression in the Perioperative Period in Women of Reproductive Age During Regional Anesthesia - O. A. Chernykh; R. E. Lakhin; A. V. Shchegolev (Неотложная медицинская помощь, 2024)
Introduction Perioperative cognitive impairment occurs in both pregnant and non-pregnant women. Prediction, early detection and effective treatment of these disorders are important for the well-being of women and their offspring.Aim of study To evaluate the effect of anesthesia and surgery on the level of anxiety, depression, short-term memory, and concentration in pregnant and nonpregnant women.Material and methods The observational prospective study included 120 patients who were divided into two equal groups — pregnant (n=60) and nonpregnant (n=60) women. A comparative analysis of testing psychosomatic reactions and cognitive functions using the MoCa test, Benton and Wechsler tests, selfassessment questionnaire, Hospital Anxiety and Depression Scale (HADS) was carried out. The relative risk and odds ratio of developing anxiety and depression were calculated.Results Anxiety indicators in pregnant women before surgery reached subclinical values of 7.5 (8.4; 6.6), and in non-pregnant women – the norm: 6.5 (7.3; 5.7) (p<0.001); Results of depression in pregnant women after surgery were 7.3 (8.5; 6.1), in non-pregnant women — the norm: 6.3 (7; 5.5) (p<0.001). The odds of developing short-term memory impairment in pregnant women before surgery was 3.1 times higher than in non-pregnant women, odds ratio 3.1 (95% CI [1.3–7.4]). In the pregnant group, short-term memory scores before surgery were 5 (5.8; 4.2), and after surgery they decreased to 3.8 (4.7; 2.9) (p<0.001). There was a decrease in concentration of attention in pregnant women: before surgery 6.2 (6.8; 5.6), and after surgery — 5 (5.8; 4.2) (p<0.001). The relative risk (RR) of developing depression in pregnant women after surgery was 6.1 times RR=6.1 (95% CI 2.4; 15.8), sensitivity Se (%)=0.9, specificity Sp (%)=0.5. The relative risk (RR) of developing short-term memory impairment after surgery was 1.1 times RR=1.1 (95% CI 1; 1.2), sensitivity Se (%)=0.5, specificity Sp (%)=0, 8. The relative risk (RR) of developing problems with concentration after surgery was 8.3 times RR=8.3 (95% CI 3.9; 18.3), sensitivity Se (%)=0.8, specificity Sp (%)=0.7.Conclusions The Results obtained allow us to conclude that before surgery, pregnant women experience a subclinical version of anxiety, against the background of which the chances of developing problems with short-term memory and concentration increase. After surgery, pregnant women experience a subclinical version of depression, along with it there is also impairment of intelligence, short-term memory and concentration. The initial impairment of memory and attention requires the selection of anesthesia in a group of pregnant women.